Estimation of Skin to Subarachnoid Space Depth: An Observational Study - Rajib Hazarika; Dipika Choudhury; Sangeeta Nath; Samit Parua (Journal of Clinical and Diagnostic Research, 2016)
Introduction: In a patient, the skin to Subarachnoid Space Depth (SSD) varies considerably at different levels of the spinal cord. It also varies from patient to patient at the same vertebral level as per age, sex and Body Mass Index (BMI). Estimation of the skin to SSD reduces complications related to spinal anaesthesia. Aim: To measure the skin to SSD in the Indian population and to find a formula for predicting this depth. Materials and Methods: Three hundred adult patients belonging to American Society of Anaesthesiologist class I and II, undergoing surgery using spinal anaesthesia in various surgical specialities of Gauhati Medical College were selected by systemic sampling for this prospective, observational study. Patients were divided into three groups: Group M containing male patients, Group F containing non-pregnant female patients, and Group PF containing pregnant female’s patients. SSD was measured after performing lumbar puncture. The relationship between SSD and patient characteristics were studied, correlated and statistical analysis was used to find a formula for predicting the skin to SSD. Statistical analysis was done using Statistical Package for Social Sciences (SPSS 21.0, Chicago, IL, USA). One-way ANOVA with post-hoc(Bonferroni correction factor) analysis was applied to compare the three groups. Multivariate analysis was done for the covariates followed by a multivariate regression analysis to evaluate the covariates influencing SSD for each group separately. Results: Mean SSD was 4.37±0.31cm in the overall population. SSD in adult males was 4.49±0.19cm which was significantly longer than that observed in female’s 4.18±0.39cm which was comparable with SSD in parturient 4.43±0.19 cm. The formula for predicting the skin to SSD in the male population was 1.718+0.077×BMI+0.632×Height, in nonpregnant female population was 1.828+0.077×BMI+0.018×Height+0.007×Age and 0.748+0.209×BMI+4.703×Height-0.054×weight in parturient females, respectively. Conclusion: Skin to SSD correlated with the BMI in all the patients in our study.